MASS TRANSFER CORRELATION FOR THE REMOVAL OF COPPER IONS FROM WASTEWATER - Kaminari, N. M. S.; Ponte, M. J. J. S.; Ponte, H. A. (Revista de Engenharia Térmica, 2010)
One of the biggest problems with ore processing in extractive metallurgical industries is the high toxicity of the heavy metals waste content (e.g., copper, lead, nickel and chrome). This work investigates the copper (II) íons removal from aqueous solutions in concentrations up to 1000 ppm. Therefore, a fluidized bed electrolytic reactor was used with flow-by configuration considered as a hopeful method due to the large specific surface area and the high mass transfer rate. The performance of the electrochemical reactor was investigated by using different porosities. Dimensionless Sherwood and Reynolds numbers were correlated to characterize the mass transport properties of the reactor, and they were fitted to the equation Sh = a.Reb.Sc1/3.